2015
DOI: 10.1159/000431353
|View full text |Cite
|
Sign up to set email alerts
|

Foveal Exudative Macroaneurysm Treated with Intravitreal Ranibizumab

Abstract: Purpose: We report a case of a foveal macroaneurysm with long-standing macular edema in a rare location, successfully treated with intravitreal ranibizumab. Methods: We report the case of a 52-year-old man with left eye long-term visual loss due to macular edema caused by a retinal macroaneurysm, localized about 400 μm from the center of the fovea, and its response to 6 monthly ranibizumab intravitreal injections. His best-corrected visual acuity and morphological data evaluated by optical coherence tomography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…However, there has been a consensus for treatment for complications such as macular edema or macular or vitreous hemorrhage [ 4 , 5 ]. For this, intravitreal injections can be considered, and there has been published data about the use of bevacizumab and ranibizumab [ 7 , 8 , 10 ]. Data concerning the use of aflibercept do not exist so far.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there has been a consensus for treatment for complications such as macular edema or macular or vitreous hemorrhage [ 4 , 5 ]. For this, intravitreal injections can be considered, and there has been published data about the use of bevacizumab and ranibizumab [ 7 , 8 , 10 ]. Data concerning the use of aflibercept do not exist so far.…”
Section: Discussionmentioning
confidence: 99%
“…Successful treatment of these lesions with intravitreal anti-VEGF therapy has already been shown in several case reports and studies [6, 7, 8, 9]. However, the pathogenesis has not been fully clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Intravitreal anti-VEGF injections are more recent therapeutic alternatives, being shown to reduce vascular permeability, normalize central retinal thickness, and lead to visual stabilization or slight improvement (1, 4–56789–10–1112131415). In our case series, intravitreal ranibizumab was found to improve visual acuity from 0.62 to 0.37 logMAR and provide anatomical recovery by decreasing macular edema from 631.4 to 256.6 μm at the long-term follow-up of 13.4 ± 3.2 months, as well as promoting the absorption of hemorrhages.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, in the era of anti-vascular endothelial growth factor (VEGF) treatment, there have been several reports suggesting the use of intravitreal bevacizumab or ranibizumab for the treatment of RAM, showing encouraging results, but having limited follow-up time (4–56789–10–1112131415). In light of the above, the purpose of this study was to evaluate the anatomical and functional results after intravitreal ranibizumab injections for the treatment of symptomatic RAM in a long-term follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…[17] Although Chatziralli et al found that only one injection was needed for resolution of macular edema, [44] other authors reported requiring more injections until fluid resolved completely. [43,45,46] The use of anti-VEGF agents does not preclude the use of laser, which Chen et al suggest may better reduce macular edema. [20] In one report, once 6 injections were performed, indirect thermal laser was applied with subsequent complete resolution of fluid.…”
Section: Pharmacologicmentioning
confidence: 99%